ANALYSIS OF INCOME LEVELS AND WELFARE OF SMALL-SCALE FISHERMEN'S HOUSEHOLDS IN BENGKULU CITY - Sudarma, Rahmat; Cahyadinata, Indra; Mulyasari, Gita; Supriyadi, Supriyadi (Universitas Mataram, 2025)
According to data from BPS (2023), the capture fisheries production in Bengkulu City reached 41,919 tons in 2022. Despite its significant potential, fishermen’s income levels are highly dependent on unpredictable, uneven, and difficult-to-forecast catch results, often leading to their classification as